2016
DOI: 10.1080/15476286.2016.1240140
|View full text |Cite
|
Sign up to set email alerts
|

Translocation as continuous movement through the ribosome

Abstract: In each round of translation elongation, tRNAs and mRNA move within the ribosome by one codon at a time. tRNA-mRNA translocation is promoted by elongation factor G (EF-G) at the cost of GTP hydrolysis. The key questions for understanding translocation are how and when the tRNAs move and how EF-G coordinates motions of the ribosomal subunits with tRNA movement. Here we present 2 recent papers which describe the choreography of movements over the whole trajectory of translocation. We present the view that EF-G a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 62 publications
0
37
0
Order By: Relevance
“…S2B). Taking into consideration that the shift occurred in a triplet manner and that deacylated tRNA should be cognate to the E-site similarly to reverse translocation in prokaryotes (23,24) we concluded that we observed reverse translocation of the eukaryotic ribosomes.…”
Section: Post Ribosomes Relocate Backwards By Three Nucleotides In Thmentioning
confidence: 71%
See 1 more Smart Citation
“…S2B). Taking into consideration that the shift occurred in a triplet manner and that deacylated tRNA should be cognate to the E-site similarly to reverse translocation in prokaryotes (23,24) we concluded that we observed reverse translocation of the eukaryotic ribosomes.…”
Section: Post Ribosomes Relocate Backwards By Three Nucleotides In Thmentioning
confidence: 71%
“…The role of hydrolysis of GTP by elongation factor 2 in the catalysis of translocation is currently under active discussion (23). The questions that need to be clarified include how hydrolysis is related to the structural rearrangements of the ribosome and the movements of tRNA, and whether the energy released in the reaction directly drives translocation.…”
Section: Introductionmentioning
confidence: 99%
“…After EF-G binding to the ribosome, the SSU head and body domains move in the same counterclockwise (CCW) direction relative to the LSU, which is referred to as forward, because it corresponds with the direction of translocation (Fig. 5) (Guo and Noller 2012;Belardinelli et al 2016b;Wasserman et al 2016). EF-G hydrolyzes GTP, but retains the Pi (Savelsbergh et al 2003(Savelsbergh et al , 2005.…”
Section: Translocationmentioning
confidence: 99%
“…Structural studies of trapped EF-G-bound translocation intermediates (19)(20)(21)(22), stopped-flow ensemble FRET experiments (23)(24)(25), and single-molecule FRET studies (9) reveal that this movement is coupled to large-scale (∼21°) rotation of the head domain of the 30S subunit ( Fig. 1).…”
mentioning
confidence: 99%